Immigration Policy and the Rise of Self-Employment among Mexican Immigrants - Catalina Amuedo-Dorantes; Magnus Lofstrom; Chunbei Wang (Institute of Labor Economics (IZA), 2020)
Over the past two decades, the U.S. has seen a drastic growth in self-employment among Mexican immigrants, the largest immigrant population in the country. This is an interesting yet puzzling trend, in stark contrast to the stagnated growth of self-employment among other disadvantaged minority groups such as blacks and even a significant decline among whites. Little is known of what drives that growth. We propose that the expansion of interior immigration enforcement, a characteristic of the U.S. immigration policy during that time span, might have contributed to this unique trend by pushing Mexican immigrants into self-employment as an alternative livelihood. Exploiting temporal and geographic variation in immigration enforcement measures from 2005 to 2017, we show that tougher enforcement has been responsible for 10 to 20 percent of the rise in Mexican self-employment. The impact mainly concentrates among likely undocumented immigrants. It is mainly driven by police-based enforcement measures responsible for most deportations, as opposed to employment-based enforcement. Our results suggest that apprehension fear, instead of lack of employment opportunities, is the main push factor.
Keywords: J15; J23; K37; 330; state and local immigration enforcement; undocumented immigrants; Mexican immigrants; self-employment; United States